Development of neuropsychiatry over the last 30 years and the new era of Immuno-Psychiatry - Karl Bechter (Journal of Affective Disorders Reports, 2023)
This is a narrative review about Neuropsychiatry, the development of Psychoneuroimmunology, and the progression to Immuno-Psychiatry (IP) over the last 30 years based on textbooks, journal articles and personal contributions.Definitions, coverage and highlights in the development of neuropsychiatry document a change from focused individual organic diagnostic case reports to broader approaches (e.g., brain-mind relationships), or more specialized (e.g., neuroimaging perspective, neurogenetics, neuroplasticity) thereby achieving increasing clinical relevance, and advancing to recent highlights those being the developments in neurogenetics and psychoneuroimmunology. The latter has culminated in the emerging field of IP.Basic new insights of IP include: a role for neuroinflammation in a spectrum of severe mental disorders, the consensus description of diagnosis and treatment of autoimmune psychosis (with outstanding clinical relevance), emerging findings of prevailing milder forms of neuroinflammation in severe mental disorders (SMD's) by emerging appropriate diagnostic methods (especially neuroimaging, CSF diagnostics), the role of environmental factors, especially infections, in the causality of SMD's. The interaction between genetic and environmental factors remains largely unresolved, with common pathophysiologic links possibly related to an IP constellation.